ANALISIS PENGARUH KUALITAS PELAYANAN PRIMA DAN KEPERCAYAAN PELANGGAN TERHADAP KEPUTUSAN PEMBELIAN KARTU TELKOMSEL DI SURABAYA BARAT - Machmuda, Dita Aulia; Andayani, Sri; Tjahjono, Endro (Jurnal Dinamika Administrasi Bisnis, 2017)
Telecommunication operator must know what are the factors that make the customer determine the decision to purchase the prime card. One only for quality services are needed in the company to win the market in the world the competition. In addition to the quality of service prima, companies can improve customer confidence that customers have a relationship with the company. The purpose of this research is to know the influence of the quality of service provision and customer trust to purchase decision Telkomsel card. Samples in this research are 100 respondents taken in Surabaya West. while the analysis methods used, multiple linear regression and hypothesis testing using F and T tests The results of this research showed that the Variable Quality of Service Provision and customer trust partially significant influence on purchasing decisions. This is known from the value of the service quality thitung Prima of 3.283 greater than ttabel (1.292), so that the research hypothesis that reads "there is the influence of the quality of service provision against the decision of the purchase of the card Telkomsel in Surabaya West", can be declared accepted. And the value of 3.011 thitung customer confidence greater than ttabel (1.292). So the research hypothesis that reads "no influence of customer trust to purchase decision Telkomsel Card in Surabaya West", can be declared accepted.Â Key Words : the Quality of Service Provision, Customer trust, Purchase Decision